The Middle Ages illustrated in La Sicilia by Gustavo Chiesi (1892) - Paola Vitolo (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2019)
La Sicilia illustrata nella storia, nell’arte, nei paesi is the account of the travel conducted in Sicily during the summer of 1890 by Gustavo Chiesi (1855-1909), journalist, author and politician from the Italian Emilia region. The work, addressed to a cultured but non-specialist audience, is a fusion of several literary genres: it is a travel account, like those of the Grand Tour, and at the same time a well-documented description of the multiple aspects of the Sicilian culture and society. The book is of great interest also for the scholars of the Middle Ages. The process of rediscovering of the Medieval history and art in Sicily had begun in the second half of the eighteenth century and, not without strong ideological conditioning, it had accompanied the Italian unification. The creation of national offices devoted to the documentation and protection of the cultural patrimony produced the first restorations and photographic campaigns. Therefore, Chiesi reserved in his book a wide space to the Middle Ages, secondary only to that for the archaeology and the ancient history. Medieval history and monuments are widely illustrated in the book, with reference to the most recent historical-critical discussions. The rich apparatus of xylographies reproduces in many cases the photos taken by the first great ateliers (Sommer, Brogi, Alinari, Incorpora ...) that contributed to spread the image of Sicily and of its artistic heritage in Italy and beyond.